Atmospheric temperature, water vapour and liquid water path from two microwave radiometers during MOSAiC - Andreas Walbröl; Susanne Crewell; Ronny Engelmann; Emiliano Orlandi; Hannes Griesche; Martin Radenz; Julian Hofer; Dietrich Althausen; Marion Maturilli; Kerstin Ebell (Scientific Data, 2022)
Measurement(s) radio wave radiation • far-infrared radiation Technology Type(s) microwave radiometer Factor Type(s) brightness temperature Sample Characteristic - Environment planetary atmosphere Sample Characteristic - Location Arctic Ocean